Designing proficiency tests to accredit previous knowledge in american and british literature in a bilingual education program (2010)
This article aims at identifying the kind of American and British literature tests that can be designed to allow students who enter a bilingual education program at a private university in Colombia to have their previous knowledge in these two subjects accredited through a proficiency test. Students’ needs, opinions, beliefs, existing commercial tests, the University’s (specifically, the one where the study was conducted) literature programs, several anthologies, and competences required in the education program were all taken into consideration. Then the tests were developed, piloted, and validated with a focus group composed of ten students of said program. The results indicated that students require previous knowledge, literary competence, and command of the English language because those are determining factors in successfully passing the tests. Key words: Previous knowledge, proficiency tests, American and British literature, competences Este artículo busca identificar un modelo óptimo para un examen de literatura americana y británica que se puede diseñar para que los estudiantes que inician el programa de educación bilingüe de una universidad privada en Colombia puedan acreditar el conocimiento previo en estas dos materias, mediante un examen de suficiencia. Para el diseño de los exámenes se tuvieron en cuenta las necesidades y opiniones de los estudiantes, así como exámenes comerciales existentes, los programas de literatura de la universidad, varias antologías y las competencias requeridas por el programa de educación. Los exámenes diseñados se pilotearon y se validaron con un grupo de 10 estudiantes del programa en mención. Se determinó que los estudiantes requieren un conocimiento previo, competencia en literatura y un nivel competitivo en inglés, para aprobar satisfactoriamente los exámenes. Palabras clave: conocimiento previo, acreditación, exámenes de literatura americana y británica, competencias